Ruminal degradability and digestibility of sugar cane leaves treated with phosphoric acid - Sánchez-Olguín , Joyce; Alejos-De la Fuente , Jóse Isidro; Torres-Hernández , Glafiro; Sosa-Montes, Dr. Eliseo; Pro-Martínez , Arturo; Bello-Olivera , Benito (Ecosistemas y Recursos Agropecuarios, 2025)
Sugarcane leaves were treated with phosphoric acid (H3PO4) and neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin (ADL), hemicellulose (Hem), cellulose (Cell), silica (S), ruminal degradability (Deg) and ruminal digestibility (Dig) were determined in sugarcane leaves. Five hundred g of leaves were impregnated with 250 mL of 0.01, 0.1 and 1.0 molar H3PO4 for 1, 3, 5 and 7 days. At day 3 with H3PO4 0.01 and 0.1 molar, NDF and ADF increased and then NDF decreased (Hem was dissolved) while ADF remained constant. At day 3 with H3PO4 1.0 molar, both variables decreased (some lignocellulosic fractions were dissolved) and NDF continued to decrease. With H3PO4 0.01, 0.1 and 1.0 molar, ADL increased at day 7 (14.78, 14.07 and 11.68%, respectively). With H3PO4 0.01 and 0.1 molar, Hem did not change with time, but Cell decreased at day 7 (31.34 and 34.17%). With H3PO4 1.0 molar from day 1 to 7, Hem and Cell decreased. With H3PO4 0.01 and 0.1 molar, S increased on day 1 (6.72 and 6.92%), and with H3PO4 1.0 molar it did not change. With H3PO4 0.01 and 0.1 molar, Deg and Dig did not change, while, with 1.0 molar on day 1, both variables increased. Conclusion: at low concentrations, H3PO4 binds to the fiber and increases it, so NDF, ADF and S increase, but at 1.0 molar (99 g L-1), it dissolves several lignocellulosic fractions of sugarcane leaves increasing their degradability and digestibility.
Keywords: hydrolysis; forage; drought; chemical treatment